Rendezvous Missions to Systems of Small Solar System Bodies Using the Suboptimal SDRE Control Approach - Cereja, Edson; Balthazar, José Manoel [UNESP]; Tusset, Angelo Marcelo; Razoumny, Vladimir; Prado, Antonio Fernando Bertachini de Almeida (MDPI, 2025)
In this work, we analyze the suitability of the State-Dependent Riccati Equation (SDRE) suboptimal nonlinear control formulation for the implementation of body-fixed hovering of a spacecraft in the highly nonlinear environment engendered by the faint force fields around single- and multi-body Near-Earth Objects (NEOs), a class of Small Solar System Bodies with high relevance either in scientific, economic, or planetary defense-related aspects. Our results, addressing the hovering of a spacecraft around relative equilibrium points on the effective potential of the Near-Earth Asteroid (16) Psyche and of the much smaller main body (called Alpha) of the triple NEA system (153591) 2001SN263, show that the known effectiveness offered by the flexibility engendered by state-dependent factorization of nonlinear models is also effective when applied in these faint and highly nonlinear force fields. In fact, this work is a qualitative evaluation of the suitability of using SDRE in the highly disturbed environment around Small Solar System Bodies, which has never been undertaken before. We intend to prove that this method is adequate. For real missions, it is necessary to make deeper studies. In particular, our results show the flexibility granted by the SDRE approach in the trade off between maneuvering time against fuel consumption, a central aspect in such space missions. For instance, our simulations showed control effort and time of convergence for two controlled trajectories around (16) Psyche ranging from a half-time convergence with ∼20 times lower cost. Analogously, for the much smaller bodies in the (153591) 2001SN263 triple system, we got two trajectories in which one of them may converge ∼10 times faster but with up to ∼100 times higher cost.
Keywords: ASTER mission; asteroid system; body-fixed hovering; Near-Earth Objects; nonlinear control; SDRE suboptimal control; small solar system bodies; state-dependent factorization